The Effect of Governance and Audit Quality on Earnings Quality in Basic Materials Sector Companies - Winastuti, Ira; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of governance and audit quality on profit quality in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The population in this study is Basic goods sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study uses a purposive sampling technique. 14 companies were obtained so that the number of samples used was 42 observation data. The analysis used in this study is multiple regression analysis using SPSS version 26 as the calculation tool. Based on the results in this study, it shows that independent commissioners have a negative effect on the quality of profits. Meanwhile, the audit committee, institutional institutions, audit quality, capital structure, and leverage have no effect on the quality of profits.